2018
DOI: 10.1002/mcda.1634
|View full text |Cite
|
Sign up to set email alerts
|

Policy analysis on the fly with an online multicriteria cardinal ranking tool

Abstract: This paper reports upon the deliverables and learnings from a project within decision analysis for participatory planning and policy analysis on the municipal level. The project aimed to develop and utilize an online multicriteria decision analysis tool for evaluations of policy alternatives with respect to municipal commercial development policies, acknowledging the objectives and preferences from various local and national stakeholders. The tool itself relied solely on that the users supplied cardinal rankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…One vital issue is the comprehensiveness regarding the recognition of the policy problem that initiates a policy process. As previous research has indicated and the findings of this study confirm, the perceptions concerning the modes of transport and the stakeholders involved are incomplete and unbalanced due to historical pathways, local circumstances and individual, institutional and societal biases [2,[89][90][91]. These conditions and incomplete assessments result in individual cognitive models regarding the policy problem, which are explainable by the iceberg theory [92]; that is, major parts of the problem are not made explicit or visible to a certain stakeholder.…”
Section: Implications For the Multi-level System Of Governancesupporting
confidence: 56%
“…One vital issue is the comprehensiveness regarding the recognition of the policy problem that initiates a policy process. As previous research has indicated and the findings of this study confirm, the perceptions concerning the modes of transport and the stakeholders involved are incomplete and unbalanced due to historical pathways, local circumstances and individual, institutional and societal biases [2,[89][90][91]. These conditions and incomplete assessments result in individual cognitive models regarding the policy problem, which are explainable by the iceberg theory [92]; that is, major parts of the problem are not made explicit or visible to a certain stakeholder.…”
Section: Implications For the Multi-level System Of Governancesupporting
confidence: 56%
“…Because of the complexity of these calculations, we use the state-of-the-art multi-criteria software tool DecideIT 3.0 for the analysis, which allows for imprecision of the kinds that exist in this case. DecideIT is based on patented algorithms [53] and several versions have been successfully used in a variety of decision situations, such as large-scale energy planning [54], allocation planning [55], demining [56], financial risks [57], gold mining [58] and many others [59].…”
Section: Multi-criteria Decision Modelling and Analysismentioning
confidence: 99%
“…There are several studies investigating specific performance aspects of interventions against pandemics but they are most often limited to a single scenario and they are seldom designed to explicitly acknowledge the inherent uncertainties in both simulation results and scenario likelihoods. We have previously applied more dynamic multi-criteria decision analysis approaches to synthesize outcome predictions and stakeholder preferences from multiple perspectives into decision recommendations (27). Applied to the COVID-19 mitigation problem, the methodological components could, for instance, be partitioned into (i) a co-creative preference elicitation component, (ii) an epidemiological component, (iii) a socioeconomic component, and (iv) an aggregation and analysis component.…”
Section: The Decision Analytical Frameworkmentioning
confidence: 99%
“…Because of the complexity in these calculations, we use the software tool DecideIT for the analysis which allows for imprecision of the kinds that exist in this case. The tool is based on patented algorithms (39) and several versions have been successfully used in a variety of decision situations, such as large-scale energy planning (37), allocation planning (27), demining (40), financial risks (41), gold mining (42), and many others (43).…”
Section: The Evaluation Processmentioning
confidence: 99%